Geographic Market Size and the Extent of Multiplant Operations - Duetsch, Larry L. (The Review of Economics and Statistics, 1982)
Kuznets, Simon, Growth and Inequality, American Economic Revtiew 45 (March 1955), 1-28. Long, James E., David W. Rasmussen, and Charles T. Haworth, Income Inequality and City Size, this REVIEW 59 (May 1977), 244-246. Paglin, Morton, The Measurement and Trend of Inequality: A Basic Revision, American Economic Review 65 (Sept. 1975), 598-609. Sale, Tom S. III, Interstate Analysis of Size Distribution of Family Income, 1950-1970, Southern Economic Journal 40 (Jan. 1974), 434-441. Smith, Donald Mitchell, and E. James Jennings, The Distribution of State Incomes: Differential Growth of Sectoral Employment,' American Economic Review 66 (Sept. 1976), 717-721. Smolensky, Eugene, Industrialization and Inequality-Recent U.S. Experience, Papers on the Regional Science Association 7 (1961), 67-88. , An Interrelationship among Distributions, this REVIEW 45 (May 1963), 197-206. Tam, Mo-Yin S., and Joseph Persky, Direct and Indirect Effects of Regional Convergence on National Inequality, University of Illinois at Chicago Circle, College of Business Administration Working Paper (1981). U.S. Bureau of the Census, Current Population Reports, Consumer Income, Series P-60, No. 118 (Mar. 1979).